2011
DOI: 10.1098/rspb.2011.0518
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian phylogenetic analysis supports an agricultural origin of Japonic languages

Abstract: Languages, like genes, evolve by a process of descent with modification. This striking similarity between biological and linguistic evolution allows us to apply phylogenetic methods to explore how languages, as well as the people who speak them, are related to one another through evolutionary history. Language phylogenies constructed with lexical data have so far revealed population expansions of Austronesian, Indo-European and Bantu speakers. However, how robustly a phylogenetic approach can chart the history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(104 citation statements)
references
References 36 publications
7
97
0
Order By: Relevance
“…In chapter 24 of this volume, linguist Alexander Vovin states that: "There is almost universal consensus that Japonic languages entered the Japanese islands via the Korean peninsula during the Yayoi period." This conclusion is further supported by a recent phylogenetic analysis of 59 Japonic languages and dialects which concluded that these languages derived from a common ancestor about 2,182 years ago (Lee & Hasegawa 2011).…”
Section: The Arrival Of the Yayoi Population In Japansupporting
confidence: 62%
“…In chapter 24 of this volume, linguist Alexander Vovin states that: "There is almost universal consensus that Japonic languages entered the Japanese islands via the Korean peninsula during the Yayoi period." This conclusion is further supported by a recent phylogenetic analysis of 59 Japonic languages and dialects which concluded that these languages derived from a common ancestor about 2,182 years ago (Lee & Hasegawa 2011).…”
Section: The Arrival Of the Yayoi Population In Japansupporting
confidence: 62%
“…Neither the phonological evidence nor the statistical evidence (in the case of Japanese) is consistent with a date of protolanguage divergence older than the dates for the beginning of wet rice agriculture, as pointed out by Hudson (1999) and Lee and Hasegawa (2011). This fact alone does not rule out the possibility that proto-Japanese descends from a preYayoi Jōmon language, or proto-Korean from a pre-Mumun Chulmun language.…”
Section: Chronological Depth Of Language Familiesmentioning
confidence: 78%
“…In a recent paper, Lee and Hasegawa (2011) attempt to overcome 10 Lee and Ramsey acknowledge that the four numerals attested in the Koguryŏ phonogrammatic tradition "all look remarkably like Japanese" (2011: 43). They then state "At the same time, however, the vocabulary found in the Koguryŏ place names includes even more elements that relate solidly to Middle Korean and thus to the mainstream development of the Korean language" (ibid).…”
Section: Chronological Depth Of Language Familiesmentioning
confidence: 99%
“…The relative influence of these three processes varies across aspects of culture. Language frequently exhibits highly tree-like patterns of vertical transmission (Bouckaert et al, 2012;Gray et al, 2009;Lee & Hasegawa, 2011), as do a variety of social practices (Currie et al, 2010;F. M. Jordan et al, 2009;Opie et al, 2014), and aspects of material culture (P. Jordan & Shennan, 2009;Larsen, 2011;Tehrani & Collard, 2002).…”
Section: Introductionmentioning
confidence: 98%